Førstefødtlæstadianernes selvrepresentasjon. En analyse av to brosjyrer - Andreassen, Bengt-Ove (Nordlit, 2012)
In 1992 and 2010 the group within the Laestadian tradition labeled “the firstborns” or “the  firstborn  group”  published  brochures  in  which  they express  their  beliefs  and identity.  Using  a  discourse  analytical approach  the  article  aims  to  examine  the  Firstborn’s selfrepresentation in these brochures. A goal is to investigate whether or not the Firstborn self-representation  has  changed  in  the  period  between  the  two  brochures. A main argument is that the group’s mediation and way of representing themselves in 2010 is characterized by a new use of established concepts which point to a possible secession from  the  Norwegian  State  Church  and the  establishment  of  a separate  independent religious organization.